Pemberdayaan Kelompok Tani Wanita Seroja Kelurahan Palas Kecamatan Rumbai Melalui Budidaya Tanaman Pinang (Arecha Catechu) Varietas Betara - Sri Utami Lestari; Seprita Lidar (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The problem faced by partners is limited knowledge about areca nut cultivation technology. Regarding partner problems, a solution to the problem is needed, including improving partners' knowledge and skills regarding areca palm cultivation technology. The method of implementation includes several stages: socialization of var.betara betel nut cultivation, provision of betara areca nut plants, cultivation practices, evaluation and for the sustainability of this program the PKM team will monitor and provide assistance during the activity. Based on the results of the team's monitoring and evaluation, the following conclusions can be drawn: Participants' attendance in the socialization activities adjusted to government regulations during the Pandemic by following health protocols where participants were limited to only a few people. Participants were very active during the activity, where participants showed good enthusiasm and enthusiasm during the discussion about the material provided related to areca var.betara cultivation and the high interest of partners in planting areca nut, indicated by the number of requests for var.betara areca seeds, after the activities of the partners had been carried out. have very satisfying knowledge and understanding to carry out betel nut cultivation activities independently in the future in their respective homes